Analisis Keterampilan Menulis Dengan Menggunakan Model Pembelajaran Course Review Horay Di Sekolah Dasar - Katrina Damayanti; Lilik Binti Mirnawati; Fitroh Setyo Putro Pribowo (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study was to analyze whether student learning outcomes in writing narrative in elementary school could be improved through the course review horay learning model. This research uses qualitative research with literature study method. Sources of data used in this study are books and journals related to writing skills using the course review horay learning model. Based on searches on Google Scholar, 10 journals were found that have been selected, the course review horay learning model can improve student learning outcomes. The course review horay learning model can not only improve the results of writing practice, but students can also understand the concept of writing skills properly and correctly because the concept of the material to be discussed can be studied in a directed manner.